Unexpected Contribution of Current Collector to the Cost of Rechargeable Al‐Ion Batteries. Issue 10 (27th May 2019) - Muñoz‐Torrero, David; Anderson, Marc; Palma, Jesús; Marcilla, Rebeca; Ventosa, Edgar
Abstract: Rechargeable aluminum‐ion batteries (AIBs) are emerging as a promising energy storage technology. However, a series of issues will need to be addressed for the commercialization of AIBs. Anodic dissolution of cheap materials commonly used as cathode current collectors is a great challenge. At laboratory scale, this issue is solved by using expensive/scarce current collectors. The aim of our work is twofold. 1) To quantify the impact of the current collector in the battery cost by performing a cost analysis, which reveals that the current collector is currently the most expensive element in AIBs. 2) To propose the use of carbon‐based current collectors, such as gas diffusion layers (GDLs), which are shown to be an excellent option for AIBs. From an electrochemical perspective, the GDL does not corrode and does not catalyze electrolyte decomposition. Moreover, performances of AIBs using GDLs as current collectors are comparable to those using more expensive state‐of‐the‐art materials, while its use contributes to reducing battery costs. Abstract : Bargain hunters : Finding suitable current collectors is a key task for the development of Al‐ion batteries. Herein, a carbon‐based material is shown to be a feasible alternative as a low‐cost material reducing the battery cost that is stable, leading to excellent electrochemical performances comparable to those of expensive materials, such as W, Ta, and Mo.